2020
DOI: 10.1093/ehjci/jeaa286
|View full text |Cite|
|
Sign up to set email alerts
|

Right atrial volume is a major determinant of tricuspid annulus area in functional tricuspid regurgitation: a three-dimensional echocardiographic study

Abstract: Aims The aim of this study is to explore the relationships of tricuspid annulus area (TAA) with right atrial maximal volume (RAVmax) and right ventricular end-diastolic volume (RVEDV) in healthy subjects and patients with functional tricuspid regurgitation (FTR) of different aetiologies and severities. Methods and results We enrolled 280 patients (median age 66 years, 59% women) with FTR due to left heart disease (LHD), pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 25 publications
3
30
0
1
Order By: Relevance
“…Notably, however, atrial volumes were independent determinants of annular areas, whereas ventricular volumes were not. These results resonate with recent publications showing that the RA dilation is the major determinant of TA size in patients with atrial fibrillation and/or functional TR (20,21). Longitudinal studies with long-term follow-up are required to establish the (patho)physiological link between exercise-induced cardiac remodeling, functional valvular regurgitation, and, eventually, occurrence of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, however, atrial volumes were independent determinants of annular areas, whereas ventricular volumes were not. These results resonate with recent publications showing that the RA dilation is the major determinant of TA size in patients with atrial fibrillation and/or functional TR (20,21). Longitudinal studies with long-term follow-up are required to establish the (patho)physiological link between exercise-induced cardiac remodeling, functional valvular regurgitation, and, eventually, occurrence of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 86%
“…5 The role of the remodeling of the right heart structures associated with lone AF in determining FTR has already been the topic of several studies. Recently, Muraru et al 15 have demonstrated the major role of the RA in determining TA size in different conditions affecting the right heart, and the direct pathophysiological link between AF, RA remodeling, and TA enlargement as a cause of FTR in a few patients with persistent AF who underwent HIGHLIGHTS Three-dimensional echocardiography is key to assess TV and right heart chamber geometry. Tricuspid annulus area is more strictly correlated with RA than ventricular size.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs with changes in RV geometry and function due to volume and/or pressure overload, such as an increase in RV volume, RV global or regional systolic dysfunction or shape abnormalities (increased sphericity, abnormal regional curvature, etc.) 3,23 . Annular dilatation is an important contributor to the development of ventricular FTR, leading to edge-to-edge leafl et coaptation 20 .…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
“…The importance of the RA has been ignored, despite the close anatomic relationship of the RA vestibule with the TV annulus. The RA vestibule is a smooth muscular rim that anchors the pectinate muscles and surrounds the TV orifi ce, with its thin musculature fibers inserting into the leafl et hinges 3 . In contrast with the MV annulus, which is disconnected from the left atrial myocardium between both fi brous trigones at the base of the anterior leafl et, the TV annulus has a single right fi brous trigone keeping it in closer contact with RA myocardium over a larger part of its circumference.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation